Download presentation

Presentation is loading. Please wait.

Published byMarvin Benson Modified over 8 years ago

1
EXAMPLE 3 Use synthetic division Divide f (x)= 2x 3 + x 2 – 8x + 5 by x + 3 using synthetic division. – 3 2 1 – 8 5 – 6 15 – 21 2 – 5 7 – 16 2x 3 + x 2 – 8x + 5 x + 3 = 2x 2 – 5x + 7 – 16 x + 3 ANSWER SOLUTION

2
EXAMPLE 4 Factor a polynomial Factor f (x) = 3x 3 – 4x 2 – 28x – 16 completely given that x + 2 is a factor. SOLUTION Because x + 2 is a factor of f (x), you know that f (– 2) = 0. Use synthetic division to find the other factors. – 2 3 – 4 – 28 – 16 – 6 20 16 3 – 10 – 8 0

3
EXAMPLE 4 Factor a polynomial Use the result to write f (x) as a product of two factors and then factor completely. f (x) = 3x 3 – 4x 2 – 28x – 16 Write original polynomial. = (x + 2)(3x 2 – 10x – 8 ) Write as a product of two factors. = (x + 2)(3x + 2)(x – 4) Factor trinomial.

4
GUIDED PRACTICE for Examples 3 and 4 Divide using synthetic division. 3. (x 3 + 4x 2 – x – 1) (x + 3) SOLUTION (x 3 + 4x 2 – x – 1) (x + 3) – 3 1 4 – 1 – 1 – 3 – 3 12 3 1 – 4 11 x 3 + 4 x 2 – x – 1 x + 3 = x 2 + x – 4 + 11 x + 3 ANSWER

5
GUIDED PRACTICE for Examples 3 and 4 4. (4x 3 + x 2 – 3x + 7) (x – 1) SOLUTION (4x 3 + x 2 – 3x + 7) (x – 1) 1 4 1 – 3 7 4 5 2 4 5 2 9 4x 3 + x 2 – 3x + 1 x – 1 = 4x 2 + 5x + 2 + 9 x – 1 ANSWER

6
GUIDED PRACTICE for Examples 3 and 4 Factor the polynomial completely given that x – 4 is a factor. 5. f (x) = x 3 – 6x 2 + 5x + 12 SOLUTION Because x – 4 is a factor of f (x), you know that f (4) = 0. Use synthetic division to find the other factors. 4 1 – 6 5 12 4 – 8 –12 1 – 2 – 3 0

7
GUIDED PRACTICE for Examples 3 and 4 Use the result to write f (x) as a product of two factors and then factor completely. f (x) = x 3 – 6x 2 + 5x + 12 Write original polynomial. = (x – 4)(x 2 – 2x – 3 ) Write as a product of two factors. = (x – 4)(x –3)(x + 1) Factor trinomial.

8
GUIDED PRACTICE for Examples 3 and 4 6. f (x) = x 3 – x 2 – 22x + 40 SOLUTION Because x – 4 is a factor of f (x), you know that f (4) = 0. Use synthetic division to find the other factors. 4 1 4 – 22 40 4 12 –40 1 3 – 10 0

9
GUIDED PRACTICE for Examples 3 and 4 Use the result to write f (x) as a product of two factors and then factor completely. f (x) = x 3 – x 2 – 22x + 40 Write original polynomial. = (x – 4)(x 2 + 3x – 10 ) Write as a product of two factors. = (x – 4)(x –2)(x +5) Factor trinomial.

Similar presentations

© 2024 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google